Evaluasi Analitik Hematology Analyzer Diatron Abacus 3 Pada Parameter Hematologi Rutin Di Laboratorium Hematologi Poltekkes Kemenkes Kalimantan Timur - Suryanata Kesuma; Mahdiah Syumarliyanty; Agus Rudi Hartono (Universitas Muhammadiyah Surabaya, 2021)
Entering the era of globalization, manual tools in clinical laboratories have been replaced by full automatic devices. One of them is the Diatron Abacus Hematology analyzer 3. A relatively new hematology analyzer is required for analytical evaluation. Analytical evaluation is an evaluation of Diatron Abacus 3 on Sysmex KX 21 as a standard in RSUD I.A Moeis Samarinda, and it is very important to do this to assess the performance of the tool. Analytical evaluation is done by determining the value of accuracy, precision, and total error and linearity of measurement results from routine hematological examination parameters, which are erythrocytes, leukocytes, platelets, hemoglobin, and hematocrit. To determine the results of the hematology analyzer evaluation of Abacus 3 Diatron Analyzers on Routine Hematology Parameters in the Hematology Laboratory of the Health Ministry of Health, East Kalimantan. This type of research is observational descriptive, using a total sampling technique, and a sample of 40 complete K3EDTA blood specimens. Data processing using Microsoft Excel and SPSS 20 applications, analyzed using descriptive statistics. The observations were still included in the criteria for acceptance, accuracy or inaccuracy (d%) in erythrocytes 1.8%, leukocytes 8.0%, platelets -5.3%, hemoglobin 2.3% and hematocrit -1.7%; Precision or impression (CV%) in erythrocytes 4.2%, leukocytes 11.1%, platelets 6%, hemoglobin 3.9% and hematocrit 4.5%; Total errors in erythrocytes were 8.7%, leukocytes 17.9%, platelets 23.6%, hemoglobin 8.8% and hematocrit 9.1; Linearity of the measurement results against the routine hematological cell count values performed using Abacus 3 and Sysmex KX 21 has a positive relationship. Acceptance values are still included in the LOA on all parameters examined and still meet the criteria; the accuracy/bias value is smaller than the true value of the parameter being examined, except for leukocytes, which is greater; the precision on the five parameters is greater than the CV% Abacus 3 insert kit; The total error obtained by the TE value is greater than the TEA in the parameters examined, except for smaller platelets; Linearity of the measurement results against the calculated hematology cell routine values performed using Abacus 3 and Sysmex KX 21 have a positive relationship, meaning an increase in measurement values using Abacus 3 is followed by an increase in measurement values using Sysmex KX 21.